Novel semiconductor low-dimensional heterostructures: formation, crystal structure and energy spectrum - Abramkin, D.S.; Bakarov, A.K.; Petrushkov, M.O.; Emelyanov, E.A.; Putyato, M.A.; Preobrazhensky, V.V.; Semyagin, B.R.; Yesin, M.Yu.; Kozhukhov, A.S.; Gutakovskii, A.K.; Shamirzaev, T.S. (Recent Contributions to Physics, 2018)
Semiconductor low-dimensional III-V heterostructures with novel energy spectrum of type-I and indirect bandgap are discussed in the paper. Charge carriers separation in reciprocal space for these structures results in localized exciton lifetime rising up to hundreds of microseconds. This is allow to investigate processes which are hard to study in direct bandgap systems with fast lifetime (~ 1 ns), for example ecxiton spin relaxation in quantum dots (QDs). The heterostructures were grown by molecular-beam epitaxy technique. Crystal structure was investigated by transmission electron microscopy. Energy spectrum was studied by steady-state and time-resolved photoluminescence spectroscopy. The experimental data supplied by calculations. It was shown, that energy spectrum of type-I and indirect bandgap forms in structures with fully relaxed GaAs/GaP and GaSb/GaP QDs and with pseudomorphically strained III-Sb/AlAs quantum wells.